Investigation of interfacial charge transfer in CuxO@TiO2 heterojunction nanowire arrays towards highly efficient solar water splitting. (20th January 2021) - Zeng, Yusheng; Xue, Jiawei; He, Mei; Li, Chuanhao; Zhu, Weiju; Li, Shikuo
Highlights: The well-defined Cux O@TiO2 nanowires with compactly phase contact are prepared by a novel integrating method. Interfacial p-n junctions promote the charge carriers separation and increase the height of CB position for hydrogen evolution. The optimal Cux O@TiO2 nanowire electrode achieves high PEC activity and stability. The mechanism of enhanced PEC performance was unraveled by XAS analysis and DFT calculation. Abstract: We investigated the interfacial charge transfer driven by the buried p-n junctions in Cux O@TiO2 nanowires for solar water splitting. The interfacial p-n junctions in the nanowire are constructed by a novel integrating in situ oxidation and thermal annealing method. The interfacial heterojunctions accelerate the transfer of photogenerated charge carriers and provide thickness controllable protective layer for Cux O nanowires suffering from photocorrsion. The optimized Cux O@TiO2 photocathode achieves a remarkable photocurrent density of -2.43 mAcm −2 at 0 V versus a reversible hydrogen electrode (RHE), which is approximately two times of the bare Cux O photocathode (-1.12 mAcm −2 at 0 V vs RHE). And the heterojunction photocathode displays a durable cathodic current with a slight decay of 9.3% over 3 h under continuous illumination. The effects of interfacial p-n junctions in Cux O@TiO2 nanowires in improving photogenerated charge carrier transfer were further disclosed by X-ray absorption spectroscopy (XAS) analysis and density functional theory (DFT) calculation. This work might afford a promising insight in understanding the mechanism of interfacial charge transfer towards designing highly efficient photoelectrodes for solar water splitting. Graphical abstract: Image, graphical abstract